Preemptive Treatment With Fibrinogen Concentrate for Postpartum Hemorrhage: Randomized Controlled Trial. Issue 1 (March 2016) - Wikkelsø, A.J.; Edwards, H.M.; Afshari, A.; Stensballe, J.; Langhoff-Roos, J.; Albrechtsen, C.; Ekelund, K.; Hanke, G.; Secher, E.L.; Sharif, H.F.; Pedersen, L.M.; Troelstrup, A.; et al.
Abstract : ( Br J Anaesth. 2015;114(4):623–633) Postpartum hemorrhage (PPH) is a major cause of maternal morbidity and mortality. In early PPH, a low concentration of fibrinogen in plasma has been linked to heavier bleeding, but it is currently unknown whether an infusion of fibrinogen concentrate can help prevent bleeding. This study is the largest randomized controlled trial to test the prophylactic effect of fibrinogen concentrate on the need for blood transfusions associated with PPH. The authors predicted that it would decrease the percentage of women in need of postpartum transfusion from 57% to 38%.